Assessing Factors That Influence Low Adoption Rate of Organic Manure in Malosa Extension Planning Area, Zomba-Malawi - Lapozo, Kneeler; Mzuza , Maureen Kapute (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
This chapter assessed the factors influencing the low adoption of organic manure in Malosa EPA Zomba, Malawi. Land degradation and desertification threaten fertile land and the benefits human society derives from its worldwide. On a global scale, around 10 - 20% of dry and 24% of the world's productive lands are degraded. The study was conducted through individual interviews and observation of 94 sampled smallholder farmers. The study used a mixed approach where both qualitative and quantitative data were collected. Qualitative data was collected on descriptive statistics about the factors influencing and motivating people to adopt organic manures in the area. In general, probability sampling methodology was used to ensure that all participants were allowed to participate equally. The findings revealed that most farmers are not using organic manure regardless of its beneficial impacts partly because of the lack of knowledge, limited livestock ownership, and lack of markets for organic manure where they must purchase the same. The study has also shown a positive relationship through the Pearson product correlation between organic manure usage and education level and knowledge of these manures' importance, which is statistically significant. Results of this study have revealed that most farmers are not using organic manure regardless of its beneficial impacts. This impact is because of the need for more knowledge, limited livestock ownership, and markets for organic manure. The study, therefore, has made the following recommendations; farmers should invest in livestock production to have adequate manure for crop production since the widely noticeable problem in the use of manure in this study is to do with the availability and accessibility of manure. Institutions should also make sure that there is a market for the manure.